The legacy of avant-gardes in social, cultural and political contexts - Štrajn, Darko (Amfiteater (Ljubljana), 2025)
As avant-gardes decisively emerged after World War I, art that was rooted in disruptive gestures found explicit expression across diverse artistic products and actions. Avant garde art increasingly aligned with revolutionary movements, tending to become an integral part of social change. However, as can be shown, avant-garde groups and trends rarely pursued any teleology of revolutionary politics. Instead, they primarily aimed to create conceptual subversions within established social orders and mindsets. Through experiences of disappointment and euphoric breakthroughs, avant-gardes developed a transcultural understanding of art and its societal role. The ultimate “success” of later avant-gardes (in the 1960s and 1970s) was manifested on both sides of the Iron Curtain. At this time, theatre and cinema expanded subversions of the “system” into actual art forms, employing signifiers of discontinuity and radically rejecting conventional codes for public messages. The world that became “subverted” was the same in Paris, Prague, Belgrade and Ljubljana. It can be argued that, under so-called real socialism, avant-gardes aligned with movements aiming to reorient the path of emancipation towards a modernist project uniting autonomous art with social freedom. Numerous cases of “experimental” theatres, films, poetry and philosophies of liberation in Yugoslavia, as in other “peripheral” countries under real socialism, exemplify this approach.
Keywords: art; družba; gledališče; liberation; osvoboditev; society; subversion; subverzija; theatre; umetnost